Test of Various Media of Antagonistic Agents Paenibacillus polymyxa Cav. Against Bacterial Leaf Blight Attack Intensity Growth and Yield of Rice Plant Varieties (Oryza sativa L.) - Yogaswara, Muhamad Agung; Komariah, Ai; Ria, Elly Roosma (Agripreneur : Jurnal Pertanian Agribisnis, 2022)
An experiment was carried out in Margasari Village, Dawuan District, Subang Regency, from July 2022 until November 2022. The purpose of this research studied the efficacy of media types of Paenibacillus antagonist agents. polymyxa in controlling Bacterial Leaf Blight on several varieties of rice plants and to obtain the most effective medium for controlling Bacterial Leaf Blight. The method used in this study was an experimental method, with a randomized block design, factorial pattern, which consisted of two treatment factors, namely factors of various Paenibacillus polymyxa media and varieties and repeated three times. The first factor was various Paenibacillus polymyxa (M) media consisting of three treatment levels, namely: m1 (Potato extract, m2 (Sweet potato extract) and m3 (Taro extract). The second factor variety (V) consisted of three levels, namely : v1 (Sidenuk), v2 (Padjajaran) and v3 (Cakrabuana). The results showed that (1) There was an interaction between P. polymyxa Antagonist Agent media on potato extract and Cakrabuana rice variation on the intensity of Bacterial Leaf Blight at 28 HST 0.09% and 35 HST 0.09% and obtained a seed weight per plot of 5.4 kg (8.64 tons ha-1) (2) Media treatment of P. Polymyxa antagonist agent on potato extract affected the intensity of Bacterial Leaf Blight, plant height. , number of productive tillers, 1000 grain weight, number of panicles clump, seed weight clump and seed weight plot (3) The cakrabuana rice variety affects the intensity of bacterial leaf blight, the number of productive tillers, the weight of 1000 grains,. the number of panicles clump and the seed weight plot, while the sidenuk rice variety was significantly different on plant height and seed weight clump